To the question of modern technologies for the collection, processing and analysis of legal statistical information - Kalguzhinova, A.M.; Amanzholova, B.A.; Ozbekov, D.O. (Bulletin of the Karaganda University “Law Series”, 2019)
The article is devoted to the consideration of the use of digital technologies features in the process of studying the disciplines of the criminal law cycle. To determine the current state of the crime counteraction, the authors reviewed the general laws of change in criminal law. The object of the research is the effectiveness of countering crime based on the analysis of state legal statistical information for the period of 2015–2017. The aim of the study is to get an idea of the stages of a statistical study (statistical observation, summary and grouping, analysis and generalization) in the criminal law field, processing and analyzing quantitative data on the state of offenses and measures of social control over them, their use in professional activities. Considering the interdisciplinary nature of the problem being studied, the dialectical, formal-logical, comparative legal, statistical, historical and legal research methods were used. The empirical base of the study was compiled by the statistical data of the Committee on Legal Statistics and Special Accounts of the General Prosecutor's Office, information materials of the Supreme Court (procedural documents of the Judicial Office service, Forum Taldau), the Ministry of Internal Affairs of the Republic of Kazakhstan. Direct analysis of official statistics data makes it possible to prepare extensive observation programs that characterize, in certain indicators, the entire course of implementation of measures of social and legal control over crime, its level, structure, dynamics, data on the identity of the perpetrator and victims.